2016
DOI: 10.1177/0306624x16652627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Restorative Justice Circles of Support and Accountability: Can Social Support Overcome Structural Barriers?

Abstract: In a climate in which stigmatic shaming is increasing for sex offenders as they leave prison, restorative justice practices have emerged as a promising approach to sex offender reentry success and have been shown to reduce recidivism. Criminologists and restorative justice advocates believe that providing ex-offenders with social support that they may not otherwise have is crucial to reducing recidivism. This case study describes the expressive and instrumental social support required and received, and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Distancing themselves from people with whom they have an established friendship might lead to potentially conflicting situations (Farrall, Hunter, Sharpe, & Calverley, 2014). Limited research has shown that, generally speaking, convicted sex offenders have minimal social support upon their community reentry (e.g., Bohmert, Duwe, & Hipple, 2016;Gutiérrez-Lobos et al, 2001). Thus, given their limited options for legitimate prosocial capital outside of their already established social network, these individuals may be particularly hesitant to move away from peers, despite their own awareness of the potentially negative impact of this network on their pathway to desistance.…”
Section: Discussionmentioning
confidence: 99%
“…Distancing themselves from people with whom they have an established friendship might lead to potentially conflicting situations (Farrall, Hunter, Sharpe, & Calverley, 2014). Limited research has shown that, generally speaking, convicted sex offenders have minimal social support upon their community reentry (e.g., Bohmert, Duwe, & Hipple, 2016;Gutiérrez-Lobos et al, 2001). Thus, given their limited options for legitimate prosocial capital outside of their already established social network, these individuals may be particularly hesitant to move away from peers, despite their own awareness of the potentially negative impact of this network on their pathway to desistance.…”
Section: Discussionmentioning
confidence: 99%
“…Restorative justice, on the contrary, views crime as a violation of the relationship between people, which concerns both victim and offender, but also broader society (Wong, Bouchard, Gravel, Bouchard, & Morselli, 2016; Zehr, 2015). The active participation of the direct involved parties—most often victim and offender—in resolving the crime is considered essential for justice to be done (Bohmert, Duwe, & Hipple, 2018; Bradshaw & Roseborough, 2005; Claessen, 2017; Umbreit et al, 2004; Zehr, 2015). It focuses on the harm that has been inflicted and the needs the involved parties have, as well as its aim is to put things as right as possible.…”
Section: Vommentioning
confidence: 99%
“…Numerous psychological and criminological explanations have been put forward to explain why participants in HSR programs in prison are less likely to recidivate. Social control theories are commonly invoked to explain the prosocial effect of religiosity, positing that individuals are less likely to recidivate if they have stronger prosocial attachments, a stake in conformity, and spend much of their time engaged in structured conventional activities (Giordano et al, 2008; Hipple, Duwe, & Northcutt Bohmert, 2016; O’Connor & Perreyclear, 2002; Schroeder & Frana, 2009; Stansfield, Mowen, O’Connor, & Boman, 2017). As an example, although Giordano et al (2008) found that neither closeness to God nor church attendance were associated with desistance, they concluded that religiosity “potentially can provide a much-needed entrée to a more prosocial network and an important layer of social support” (p. 22).…”
Section: Explaining the Relationmentioning
confidence: 99%
“…Furthermore, the faith community can help nurture feelings of acceptance, self-esteem, empathy, hope for the journey ahead, as well as redemption (Armour, Windsor, Aguilar, & Taub, 2008; Camp, Daggett, Kown, & Klein, 2008; Hipple et al, 2016; Kerley, Matthews, & Schulz, 2005). A recent study of Louisiana’s prison seminary program revealed the value people in prison place on feeling accepted, self-perception, and positive self-identity (Hallett et al, 2017).…”
Section: Explaining the Relationmentioning
confidence: 99%
See 1 more Smart Citation